Navigating Rarity: Pathological Challenges and Diagnostic Ambiguity in Rare Gliomas—A Case Series with a Focus on Personalized Treatment and Quality of Life - Nadja Grübel; Anika Wickert; Felix Sahm; Bernd Schmitz; Anja Osterloh; Rebecca Kassubek; Ralph König; Christian Rainer Wirtz; Jens Engelke; Andrej Pala; Mona Laible (Onco)
Gliomas are incurable, heterogeneous brain tumors, with rare forms often constituting diagnostic and treatment challenges. Molecular diagnostics, mainly implemented through the World Health Organization (WHO) 2021 guidelines, have refined the classification, but highlight difficulties in diagnosing rare gliomas remain. This case series analyzes four patients with rare gliomas treated at the University Hospital, Ulm, between 2002 and 2024. Patients were selected based on unique histopathological features and long-term clinical follow-up. Clinical records, imaging, and histological data were reviewed. Molecular diagnostics followed WHO 2021 guidelines. Quality of life was assessed using standardized tools including the EQ-5D-5L, EQ VAS, the Distress Thermometer, and the Montreal Cognitive Assessment (MoCA). In the first case, a 51-year-old male’s diagnosis evolved from pleomorphic xanthoastrocytoma to a high-grade glioma with pleomorphic and pseudopapillary features, later identified as a neuroepithelial tumor with a PATZ1 fusion over 12 years. Despite multiple recurrences, extensive surgical interventions led to excellent outcomes. The second case involved a young female with long-term survival of astroblastoma, demonstrating significant improvements in both longevity and quality of life through personalized care. The third case involved a patient with oligodendroglioma, later transforming into glioblastoma, emphasizing the importance of continuous diagnostic reevaluation and adaptive treatment strategies, contributing to prolonged survival and quality of life improvements. Remarkably, the patient has achieved over 20 years of survival, including 10 years of being both therapy- and progression-free. The fourth case presents a young woman with neurofibromatosis type 1, initially misdiagnosed with glioblastoma based on histopathological findings. Subsequent molecular diagnostics revealed a subependymal giant cell astrocytoma-like astrocytoma, highlighting the critical role of early advanced diagnostic techniques. These cases underscore the importance of precise molecular diagnostics, individualized treatments, and ongoing diagnostic reevaluation to optimize outcomes. They also address the psychological impact of evolving diagnoses, stressing the need for comprehensive patient support. Even in complex cases, extensive surgical interventions can yield favorable results, reinforcing the value of adaptive, multidisciplinary strategies based on evolving tumor characteristics.